Design details for overdose education and take‐home naloxone kits: Codesign with family medicine, emergency department, addictions medicine and community. (31st July 2022) - Sellen, Kate; Goso, Nick; Halleran, Laura; Mulvale‐Fletcher, Alison; Sarmiento, Felipe; Ligabue, Filipe; Handford, Curtis; Klaiman, Michelle; Milos, Geoffrey; Wright, Amy; Charles, Mercy; Sniderman, Ruby; et al.
Abstract: Introduction: Overdose education and naloxone distribution (OEND) programmes equip and train people who are likely to witness an opioid overdose to respond with effective first aid interventions. Despite OEND expansion across North America, overdose rates are increasing, raising questions about how to improve OEND programmes. We conducted an iterative series of codesign stakeholder workshops to develop a prototype for take‐home naloxone (THN)‐kit (i.e., two doses of intranasal naloxone and training on how to administer it). Methods: We recruited people who use opioids, frontline healthcare providers and public health representatives to participate in codesign workshops covering questions related to THN‐kit prototypes, training on how to use it, and implementation, including refinement of design artefacts using personas and journey maps. Completed over 9 months, the workshops were audio‐recorded and transcribed with visible results of the workshops (i.e., sticky notes, sketches) archived. We used thematic analyses of these materials to identify design requirements for THN‐kits and training. Results: We facilitated 13 codesign workshops to identify and address gaps in existing opioid overdose education training and THN‐kits and emphasize timely response and stigma in future THN‐kit design. Using an iterative process, we created 15 prototypes, 3 candidate prototypes and a final prototype THN‐kit from the synthesis of the codesign workshops. Conclusion: The final prototype is available for a variety of implementation and evaluation processes. The THN‐kit offers an integrated solution combining ultra‐brief training animation and physical packaging of nasal naloxone to be distributed in family practice clinics, emergency departments, addiction medicine clinics and community settings. Patient or Public Contribution: The codesign process was deliberately structured to involve community members (the public), with multiple opportunities for public contribution. In addition, patient/public participation was a principle for the management and structuring of the research team.